2021
DOI: 10.3390/jcm10194503
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Incidence and Associates of Pulmonary Hypertension Complicating Type 2 Diabetes: Insights from the Fremantle Diabetes Study Phase 2 and National Echocardiographic Database of Australia

Abstract: There is a paucity of epidemiologic data examining the relationship between pulmonary hypertension (PH) and diabetes. The aim of this study was to determine prevalence, incidence and associates of PH complicating type 2 diabetes. Data from 1430 participants (mean age 65.5 years, 51.5% males) in the Fremantle Diabetes Study Phase 2 (FDS2) were linked with the National Echocardiographic Database of Australia (NEDA) to ascertain the prevalence and incidence of PH (estimated right ventricular systolic pressure (eR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Li et al (2007) reported that the risk of PAH was two times higher in individuals with thyroid disease (OR, 2.53; 95% confidence interval, 1.55 to 4.08; p < 0.001) [30]. The prevalence of PAH was shown to be increased by up to 50% in type 2 diabetes [31]. Based on these studies, we identified a population with a combination of risk factors for PAH (hypertension, diabetes, thyroid problems, abnormal uric acid level, and insulin resistance) in the National Health and Nutrition Examination Survey (NHANES) to determine whether or not they had a higher level of exposure to PCBs.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2007) reported that the risk of PAH was two times higher in individuals with thyroid disease (OR, 2.53; 95% confidence interval, 1.55 to 4.08; p < 0.001) [30]. The prevalence of PAH was shown to be increased by up to 50% in type 2 diabetes [31]. Based on these studies, we identified a population with a combination of risk factors for PAH (hypertension, diabetes, thyroid problems, abnormal uric acid level, and insulin resistance) in the National Health and Nutrition Examination Survey (NHANES) to determine whether or not they had a higher level of exposure to PCBs.…”
Section: Introductionmentioning
confidence: 99%
“…In people with diabetes, the risk of PH is increased [17,18] and the available evidence suggests that it carries a particularly poor prognosis [19,20]. Whether the presence of an eRVSP >30 mmHg, which was present in approximately one-third of community-based individuals with type 2 diabetes who had undergone echocardiography as part of routine clinical care [21], has the same prognostic significance as in the general population is unknown. The aims of the present study were, therefore, to determine the eRVSP threshold associated with increased mortality in well-characterised type 2 diabetes and to explore its demographic and clinical predictors.…”
Section: Introductionmentioning
confidence: 99%
“…13 In the Fremantle Diabetes Study, analysis of the subset of persons with T2D who had echocardiograms obtained for clinical reasons showed 6.4% and 2.6% prevalence of estimated right ventricular systolic pressure >30 and >40, respectively, and over 6.6-year follow-up an additional 9.2% and 5.0% developed this degree of PH, suggesting that the risk of PH is approximately 40% greater among persons with diabetes. 14 A study of patients with PH having versus not having diabetes showed that the former had higher BNP, shorter 6-min walking distance, more dyspnea, higher pulmonary artery pressure, and shorter survival, 15 and a study of 110 563 persons with newly diagnosed PH in the US national Veterans Health Affairs database showed that more than one third had diabetes, which was associated with a 1.21-fold greater mortality risk. 16 Genetic association studies in a population of 14 861 persons with echocardiogram-measured pulmonary pressure and right ventricular function suggest both T2D and obesity to be associated with greater levels of tricuspid regurgitation and right ventricular systolic pressure, suggesting both to play roles in the development of PH.…”
mentioning
confidence: 99%
“…Insulin resistance has been proposed as underlying the relationship between diabetes and PH, with consequent inflammation, dyslipidemia, and endothelial dysfunction leading to adverse pulmonary vascular remodeling and to right ventricular dysfunction 13 . In the Fremantle Diabetes Study, analysis of the subset of persons with T2D who had echocardiograms obtained for clinical reasons showed 6.4% and 2.6% prevalence of estimated right ventricular systolic pressure >30 and >40, respectively, and over 6.6‐year follow‐up an additional 9.2% and 5.0% developed this degree of PH, suggesting that the risk of PH is approximately 40% greater among persons with diabetes 14 . A study of patients with PH having versus not having diabetes showed that the former had higher BNP, shorter 6‐min walking distance, more dyspnea, higher pulmonary artery pressure, and shorter survival, 15 and a study of 110 563 persons with newly diagnosed PH in the US national Veterans Health Affairs database showed that more than one third had diabetes, which was associated with a 1.21‐fold greater mortality risk 16 .…”
mentioning
confidence: 99%